Analisis kemiskinan di Provinsi Kepulauan Bangka Belitung - Ardhana, Fade (Economics, Finance, and Business Review, 2025)
In Indonesia and also in other developing countries, poverty is still a major problem. The government has done many things to reduce poverty rates. One of the provinces in Indonesia that has a low poverty rate is the Bangka Belitung Islands Province. This study aims to analyze the effect of GRDP, Education, Infrastructure, and Government Expenditure on Poverty in the Bangka Belitung Islands Province. There are 6 districts and 1 city studied in this study with a research period from 2017-2022. The research method used in this study is panel data regression analysis. The results of the study show that GRDP has a positive effect on poverty. Education and Government Expenditure have a negative effect on Poverty in the Bangka Belitung Islands Province. Infrastructure in the form of road length does not affect Poverty in the Bangka Belitung Islands Province. The results of the study show that local government expenditure has the greatest influence in reducing poverty. The implication is that local governments must plan carefully and spend efficiently and focus on spending on education so that they can reduce the number of poor people effectively.